2023
DOI: 10.1039/d2rp00132b
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of reasoning – exploring the interplay of students’ work with a scaffold and their conceptual knowledge in organic chemistry

Abstract: Reaction mechanisms are a core component of organic chemistry. Being able to handle these mechanisms is a central skill for students in this discipline. Diagnosing and fostering mechanistic reasoning is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 71 publications
(113 reference statements)
0
17
0
Order By: Relevance
“…Several analogous variations of constructed-response items have been reported in the literature for prompting learners to describe what is happening and why for a range of reaction mechanisms Sevian and Talanquer, 2014;Cooper et al, 2016;Caspari et al, 2018a;Crandell et al, 2018Crandell et al, , 2020Dood et al, 2018;Bode ´et al, 2019;Graulich et al, 2019;Deng and Flynn, 2021;Kranz et al, 2023;Yik et al, 2023). While not exclusive to such purposes, these constructed-response items have been presented for use as formative assessments, for promoting learning, and for instructors to respond in real time to the measured learning (Dood et al, 2018(Dood et al, , 2020aYik et al, 2021).…”
Section: Assessing Reaction Mechanisms Learningmentioning
confidence: 98%
“…Several analogous variations of constructed-response items have been reported in the literature for prompting learners to describe what is happening and why for a range of reaction mechanisms Sevian and Talanquer, 2014;Cooper et al, 2016;Caspari et al, 2018a;Crandell et al, 2018Crandell et al, , 2020Dood et al, 2018;Bode ´et al, 2019;Graulich et al, 2019;Deng and Flynn, 2021;Kranz et al, 2023;Yik et al, 2023). While not exclusive to such purposes, these constructed-response items have been presented for use as formative assessments, for promoting learning, and for instructors to respond in real time to the measured learning (Dood et al, 2018(Dood et al, , 2020aYik et al, 2021).…”
Section: Assessing Reaction Mechanisms Learningmentioning
confidence: 98%
“…Taken together, mechanistic reasoning, with or without ML techniques, can only be assessed, if prompts elicit the desired, reasoning skills. Recent studies in chemistry education research have shown the effectiveness of scaffolded prompts (Cooper et al, 2016;Caspari and Graulich, 2019;Graulich and Caspari, 2020;Watts et al, 2021;Kranz et al, 2023). According to these findings, ML-related studies should pay attention to the structure and wording of prompts to collect evidence of mechanistic reasoning.…”
Section: Prompt Structure In Ml-detected Reasoningmentioning
confidence: 99%
“…This study collected data using semi-structured interviews in the form of case comparison tasks. Case comparison tasks have been previously used to identify all relevant variables to the task (Alfieri et al, 2013) in chemistry education literature (e.g., Kranz et al, 2023). While preparing and organizing semi-structured interviews, we considered not only students' learning experiences during organic chemistry classes but also fundamental concepts required to understand stability, acidity, and basicity.…”
Section: Data Collectionmentioning
confidence: 99%